Beyond the veil of ignorance: The influence of direct democracy on the shadow economy - Friedrich Schneider; Désirée Teobaldelli (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper we analyze the influence of direct democratic institutions on the size and development of the shadow economies. The framework developed predicts a negative relationship between the degree of direct democracy and the size of the shadow economy. Countries where direct democratic institutions support democratic life are expected to be characterized by a lower informal sector, ceteris paribus. The empirical / econometric investigation of a sample of 56 democracies confirms our core hypothesis and demonstrates that the effect of direct democratic institutions on the shadow economy is negative and quantitatively important; the results are robust and also depend on the interaction of direct democracy with other political institutions, such as district magnitude.
Keywords: O17; D78; H11; H26; 330; shadow economy; direct democratic institutions; district magnitude; good governance; Schattenwirtschaft; Demokratie; Partizipation; Good Governance; Schätzung; Welt